Curcumin, Curcumin Nanoparticles and Curcumin Nanospheres: A Review on Their Pharmacodynamics Based on Monogastric Farm Animal, Poultry and Fish Nutrition - Mohammad Moniruzzaman; Taesun Min (MDPI AG, 2020)
Nanotechnology is an emerging field of science that is widely used in medical sciences. However, it has limited uses in monogastric farm animal as well as fish and poultry nutrition. There are some works that have been done on curcumin and curcumin nanoparticles as pharmaceutics in animal nutrition. However, studies have shown that ingestion of curcumin or curcumin nanoparticles does not benefit the animal health much due to their lower bioavailability, which may result because of low absorption, quick metabolism and speedy elimination of curcumin from the animal body. For these reasons, advanced formulations of curcumin are needed. Curcumin nanospheres is a newly evolved field of nanobiotechnology which may have beneficial effects in terms of growth increment, anti-microbial, anti-inflammatory and neuroprotective effects on animal and fish health by means of nanosphere forms that are biodegradable and biocompatible. Thus, this review aims to highlight the potential application of curcumin, curcumin nanoparticles and curcumin nanospheres in the field of monogastric farm animal, poultry and fish nutrition. We do believe that the review provides the perceptual vision for the future development of curcumin, curcumin nanoparticles and curcumin nanospheres and their applications in monogastric farm animal, poultry and fish nutrition.